Conservation Buru Language: Preservation Efforts To Local Language - Nanik Handayani (Al-Lisan: Jurnal Bahasa, 2021)
The condition of the hurried language is increasingly experiencing shiftsthat can lead to extinction. This study aims to (1) reveal the Buru languagecondition during society, (2) determine the factors causing the change in the Burulanguage, and (3) find solutions to tackle the Buru language from the threat ofextinction. This study is a type of field research with a qualitative approach anduses phenomenology design. This study was conducted in Namlea District, BuruRegency. Data are collected by means of interviewing, recording, anddocumentation techniques then analyzed using reduction, presentation, verification,and conclusion methods. The results show that the condition of the languagerushed from time to time has experienced a shift. Of course, this impacts the purityof the Buru language itself if it is not addressed immediately. One of the causes ofthe change in Buru's speech is that most of the interviewed informants stated thatthey no longer used hastened language in their life. Based on this, the solution thatcan be done to save the Buru language from the threat of extinction is to conservethe Buru language by intensifying the Buru language's use in various aspects oflife.